Penerapan Tari Kreasi Untuk Mengembangkan Kemampuan Motorik Kasar Anak Usia 5-6 Tahun - Pipin Rejeki; Abdul Baits (Bildung: Jurnal Ilmu Pendidikan, 2025)
This study was conducted with the aim of improving the gross motor development of 5-6 year old children at Bhakti Winaya Sodonghilir Kindergarten in Tasikmalaya through the implementation of creative dance activities. The background of this study was based on preliminary findings that showed that children's gross motor development was not yet optimal. This study used a qualitative approach involving observation and documentation in its data collection techniques. The type of research used was Classroom Action Research (CAR), conducted in two cycles and involving 12 children aged 5-6 years as subjects. Initial observation results showed low achievement in children's gross motor skills. In the first cycle, despite undergoing planning, implementation, observation, and reflection stages, the target improvement was not fully achieved. However, after adjusting the strategies and activities in the second cycle, there was a significant improvement, with an average achievement of 83% in the categories of developing as expected (BSH) and developing very well (BSB). These findings indicate that the effective implementation of creative dance can support the development of gross motor skills in young children and contribute significantly to research on the development of motor skills in young children.